AN INTEGRATED TEACHER-ALUMNI-STUDENT INFORMATION SYSTEM FOR DATA-DRIVEN CURRICULUM MANAGEMENT: A DEVELOPMENT AND FEASIBILITY STUDY AT AN INDONESIAN SENIOR HIGH SCHOOL - Hartono Hartono; Nurkolis Nurkolis; Rosalina Br. Ginting (Universitas HKBP Nommensen, 2026)
The increasing digital transformation of educational institutions has intensified the need for integrated school information systems that extend beyond administrative automation to support evidence-based curriculum management. Despite the widespread adoption of digital technologies in schools, most existing information systems operate in isolated functional domains, resulting in fragmented management of teacher, student, academic, and alumni data. This fragmentation constrains the availability of comprehensive and timely information required for curriculum planning, implementation, monitoring, and continuous improvement. Grounded in the principles of Educational Management Information Systems (EMIS) and data-driven decision-making, this study aimed to develop and evaluate an integrated Teacher, Student, and Alumni Information System (SIGANSA) to strengthen curriculum management through centralized and real-time educational data. The study employed a Research and Development (R&D) approach based on the Four-D (4D) model, comprising the Define, Design, Develop, and Disseminate phases. Data were collected through observations, semi-structured interviews, documentation, and questionnaires, while the system was evaluated by 80 teachers and educational staff to assess its practicality and feasibility. The developed system successfully integrates teacher administration, student records, academic management, and alumni tracer study data within a unified web-based platform, enabling comprehensive educational data management across multiple administrative functions. Evaluation results demonstrated a practicality score of 93.45% and a feasibility score of 97.92%, indicating that the system is highly practical and highly feasible for institutional implementation. Beyond demonstrating successful system development, this study contributes empirical evidence that integrating multi-dimensional educational data into a unified information system enhances the capacity of schools to implement data-driven curriculum management, thereby supporting more informed curriculum planning, implementation, monitoring, and evaluation. These findings underscore the strategic role of integrated educational information systems in advancing digital transformation, strengthening institutional governance, and improving curriculum management practices in secondary education.